Orthodontically induced external apical root resorption of mandibular anteriors after use of ForsusTM and AdvansyncTM 2- A CBCT study - Bhagchandani, Jitendra; Raghav, Pradeep; Reddy, Munish; Singh, Ayushi; Raj, Stuti; Chauhan, Ashish (Journal of Neonatal Surgery, 2025)
Background- Class II malocclusion is a common skeletal discrepancy which may be managed through various treatment modalities, including fixed functional appliances like AdvanSyncTM and ForsusTM FRD, widely used for non-compliant patients . However, one of the significant concerns associated with these appliances wasorthodontically induced external apical root resorption (OIEARR).This study aimed to evaluate and compare the degree of orthodontically induced external apical root resorption in skeletal Class II patients treated with Forsus™ and AdvanSync™ 2 fixed functional appliances using Cone Beam Computed Tomography (CBCT). Materials and Methods-The study involved 20 patients with skeletal Class II malocclusions (true mandibular retrusion), divided into two groups of 10 each. CBCT scans were taken before and after 6–12 months of fixed functional treatment with AdvanSync™ 2 (Group I)and Forsus™ (Group II) to assess root resorption and tooth inclination changes. Statistical analysis was performed using the Wilcoxon signed-rank test and the Mann–Whitney U test. Results- Root resorption was observed in all patients, with Forsus™ demonstrating a significantly higher mean root resorption compared to AdvanSync™ 2. The highest values were recorded for mandibular canines, with statistically significant differences between the two groups. Additionally, both appliances caused an increase in mandibular incisor proclination, but Forsus™ resulted in greater inclination changes compared to AdvanSync™ 2. Conclusion-AdvanSync™ 2 and Forsus™ are both effective in treating skeletal Class II malocclusion by facilitating mandibular advancement. However, the extent of orthodontically induced external apical root resorption (OIEARR) differs significantly between the two appliances, with Forsus™ demonstrating a higher predisposition for root resorption. These findings underscore the importance of careful appliance selection based on patient-specific factors